MEKANISME PENERBITAN AKTA PEMISAHAN RUMAH SUSUN SEBAGAI ALAS HAK LAHIRNYA SHM SARUSUN/SKBG SARUSUN BERIKUT PERALIHAN DAN PEMBEBANANNYA - WIDYANTARI, DESY EKA (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 1 No 1 (2012)DO - 10.24843/JMHU.2012.v01.i01.p02, 2012)
Deed of High-Rise Separation is an important stage in the development and ownership of high-rise because deed of separation is proof of high-rise separation upon high-rise units, mutual parts, mutual objects and mutual land with clear report in the form of drawings, descriptions and boundaries in vertical and horizontal directions which containing proportional comparison value. Proportional comparison value is very important for the owner of high-rise unit because it represents the owner’s rights and obligations on ownership, maintenance and management of such high-rise. Proportional comparison value is a number that indicates the ratio high-rise unit towards the rights over mutual parts, mutual objects and mutual land, calculated based on total area and value of the concerned high-rise unit towards the building total area or the high-rise overall value at the first time the developer calculates its overall development cost to determine its selling price. In relation to the issue of deed of separation, some problems raised as follow; firstly, its legal consequences if there is changes on building plan in further stage during the high-rise development which results in changes on proportional comparison value of the Deed of High-Rise Separation, and secondly, whether strata unit and Strata title / Building title can be used as credit security and how is the implementation of partial revocation mortgage in high-rise construction credit. A research is designed as normative legal research in order to respond those problems by using 2 types of approaches that consists of: The Statue Approach and The Legal Content Analitical Approach. The legal materials analyzed herein are primary legal material and secondary legal material, arranged descriptively and systematically. Research shows that it is possible for the high-rise developer to change the building plan provided that before making any changes on the building plan, it must inform such changes to the Association of High-Rise Residents and also has received approval from the Association of High-Rise Residents, especially if such changes result in changes of the high-rise comparison value. High-rise and high-rise unit can also be used as debt security through Mortgage/Fiduciary Institution, which allows the developer to pledge the high-rise for construction credit, in which the high-rise unit that has been fully paid by its owner can be released from the credit security of high-rise construction, thus the high-rise owner may then transfer their high-rise unit for credit security of apartment ownership (KPA) as well as other financing credit security.
Keywords: Deed of Separation, Proportional Comparison Value, Mortgage/Fiduciary Credit